TOEIC Smart :green book listening. : green book listening. (Nxb. Tổng hợp Tp.HCM : Nhân Trí Việt, 2012)
Lesson 1: Sound linking; Lesson 2: Sounds/s/and/∫/; Lesson 3: Sounds/s/and/θ/; Lesson 4: Sounds/e/and/æ/; Lesson 5: Sounds/i/and/i:/; Lesson 6: Assimilation and sound linking - Weak vowels; Lesson 7: Assimilation and sound linking - Sound/-nt-/Between vowels; Lesson 8: Assimilation and sound linking - Sound/j/; Achievement test; and answer key.